Heterogeneous Aging Within PEMFC Stacks. Issue 4 (2nd May 2014) - Chatillon, Y.; Bonnet, C.; Lapicque, F.
Abstract Evaluation of PEM fuel cell aging occurring in various operating conditions is usually conducted in single cell configuration for which various electrochemical methods can be used. Aging phenomena in stack is often investigated either in a global manner or by basic measurements of variables, e.g. individual cell voltages. This paper presents the results of aging investigation of three‐cell stacks using crossed linked electrochemical methods giving access to the time variations of ohmic and charge transfer resistance of the three cathodes, as well as the electrochemical surface area and the fuel crossover over more than 1, 000 h at 0.3 A cm–2 upon air humidification. Consistency between the various methods employed was discussed and demonstrated. In addition to the case of a stack formed by three sane cells, the case of a stack comprising a defective cell – previously aged under oxidative conditions – placed between two sane MEAs was investigated: the pre‐ageing of this cell was shown to slightly accelerate the aging under long‐term operation. Besides, it was observed that in both stacks, the back cell – i.e. located far from the stack inlet and outlet – suffered much more from the long‐term run than the two other cells.